A Unique Case of Complete Atrioventricular Block Rapidly Progressing to Diastolic and Systolic Dysfunction in Cardiac Sarcoidosis - Chimezie U. Mbachi; Oyintayo Ajiboye; Olisa Ezegwu; Benjamin Mba (Case Reports in Medicine)
Sarcoidosis is a multisystem granulomatous disease that most commonly affects the lungs but can affect other organs including the heart due to granuloma infiltration. Atrioventricular block is a common manifestation of cardiac sarcoidosis which can progress to sudden cardiac death. We report a case of cardiac sarcoidosis presenting as complete heart block, progressing to diastolic and systolic dysfunction without extracardiac manifestations early in the disease. This case stresses the importance of having a high index of suspicion for cardiac sarcoidosis in patients presenting with atrioventricular block of unknown etiology.